Aa TFL1 Confers an Age-Dependent Response to Vernalization in Perennial Arabis alpina([W])([OA]) - Wang, Renhou (American Society of Plant Biologists, 2011)
Flowering of many plants is induced by environmental signals, but these responses can depend on the age of the plant. Exposure of Arabidopsis thaliana to vernalization (winter temperatures) at germination induces flowering, whereas a close perennial relative Arabis alpina only responds if exposed when at least 5 weeks old. We show that vernalization of these older A. alpina plants reduces expression of the floral repressor PEP1 and activates the orthologs of the Arabidopsis flowering genes SOC1 (Aa SOC1) and LFY (Aa LFY). By contrast, when younger plants are vernalized, PEP1 and Aa SOC1 mRNA levels change as in older plants, but Aa LFY is not expressed. We demonstrate that A. alpina TFL1 (Aa TFL1) blocks flowering and prevents Aa LFY expression when young plants are exposed to vernalization. In addition, in older plants, Aa TFL1 increases the duration of vernalization required for Aa LFY expression and flowering. Aa TFL1 has similar functions in axillary shoots, thus ensuring that following a flowering episode vegetative branches are maintained to continue the perennial life cycle. We propose that Aa TFL1 blocks flowering of young plants exposed to vernalization by setting a threshold for a flowering pathway that is increased in activity as the shoot ages, thus contributing to several perennial traits.